Microsoft’s million-tonne CO2-removal purchase — lessons for net zero - Joppa, Lucas; Luers, Amy; Willmott, Elizabeth; Friedmann, S. Julio; Hamburg, Steven P.; Broze, Rafael (Nature, 2021)
A Nature paper describing lessons learnt from Microsoft’s removal of 1.3 million tonnes of carbon dioxide, the largest corporate purchase of carbon removal so far. Three key lessons: (1) current supply of carbon removal solutions is much smaller than what is needed to reach net-zero emissions by 2050; (2) there is a lack of standards and clear definitions for carbon removal; (3) current accounting systems do not distinguish between short- and long-term storage of CO2.